A novel splice variant of LOXL2 promotes progression of human papillomavirus–negative head and neck squamous cell carcinoma. Issue 4 (13th November 2019) - Liu, Chao; Guo, Theresa; Sakai, Akihiro; Ren, Shuling; Fukusumi, Takahito; Ando, Mizuo; Sadat, Sayed; Saito, Yuki; Califano, Joseph A.
Abstract : Background: Head and neck squamous cell carcinoma (HNSCC) is one of the most frequently diagnosed cancers worldwide. LOXL2 demonstrates alternative splicing events in patients with human papillomavirus (HPV)–negative HNSCC. The current study explored the role of a dominant LOXL2 variant in HPV‐negative HNSCC. Methods: Expression of the LOXL2 variant was analyzed using The Cancer Genome Atlas cohorts and validated using quantitative reverse transcriptase–polymerase chain reaction in a separate primary tumor set. The authors defined the effect of LOXL2 splice variants in assays for cell proliferation using a cell viability assay and colony formation assay. Cell migration and invasion were examined using a cell scratch assay and transwell cell migration and invasion assay in LOXL2 splice variant gain and loss of expression cells. Western blot analysis and gene set enrichment analysis were used to explore the potential mechanism of the LOXL2 splice variant in HPV‐negative HNSCC. Results: Expression of a novel LOXL2 variant was found to be upregulated in The Cancer Genome Atlas HPV‐negative HNSCC, and confirmed in the separate primary tumor validation set. Analyses of loss and gain of function demonstrated that this LOXL2 variant enhanced proliferation, migration, and invasion in HPV‐negative HNSCC cells and activated the FAK/AKT pathway. A total of 837 upregulated and 820 downregulated genes and 526 upregulated and 124 downregulated pathways associated with LOXL2 variant expression were identified using gene set enrichment analysis, which helped in developing a better understanding of the networks activated by this LOXL2 variant in patients with HPV‐negative HNSCC. Conclusions: The novel LOXL2 variant can promote the progression of HPV‐negative HNSCC, in part through FAK/AKT pathway activation, which may provide a new potential therapeutic target among patients with HPV‐negative HNSCC. Abstract : Head and neck squamous cell carcinoma (HNSCC) is one of the most frequently diagnosed cancers worldwide. A novel LOXL2 variant can promote the progression of human papillomavirus–negative HNSCC, which has great potential for the identification of specific targets that may be amenable to novel therapeutic targeting and expands the understanding of HNSCC carcinogenesis.